Macro-Econometric Model for Medium-Term Socio-Economic Development Planning in Vietnam. Part 2: Application of the Model - Thanh, Do Van (Economy of Regions, 2019)
Vietnam is building the market economy while still determining development plans as important tools for managing and operating the economy. In response to the challenges posed by economic globalization, the Vietnamese government has established the necessity to promote the macro economic analysis and forecasting for ensuring the government’s policy-making and socio-economic development planning. A macro-econometric model for medium-term socio-economic development planning in Vietnam was built and called the Vietnam’s model. This paper answers the following questions: which key applications can be implemented using the model? What is the model’s quality of forecasts? The paper briefly presents how to forecast using the model. Then, I demonstrate how to synthesise, validate, balance and combine the model’s forecasts implemented by the ministries and provincial authorities, and with application of judgemental methods. I establish the ways to build baseline and target forecast scenarios. The paper shows how the model can evaluate shocks and economic policies. Additionally, I demonstrate how to adjust planned target indicators in the process of implementing the medium-term socio-economic development plan. The article also evaluates the accuracy of the model’s ex-ante forecasts. Finally, I apply the model’s ex-ante forecasts for producing the official forecasts for building the Socio-Economic Development Plan (SEDP) at national scope for the period from 2016 to 2020.